Conversations with Gatekeepers: An Exploratory Study of Agricultural Publication Editors' Decisions to Publish Risk Coverage - Katie M. Abrams; Courtney A. Meyers (Journal of Applied Communications, 2010)
The United States’ agriculture industry is impacted by numerous financial, human, legal, and production risks. These risks are frequently reported in mass media and agricultural publications. Farmers often use agricultural magazines to help them make production decisions and learn about new technology, which both involve some element of risk. Gatekeeping is the process of determining what information is included in media coverage in which editors serve as gatekeepers and make decisions regarding what topics to report. The purpose of this study was to discover how agricultural publication editors, in their role as gatekeepers, make decisions regarding coverage of risk related to agriculture and to explore the forces that influence this coverage. Researchers interviewed seven purposively selected editors of national or regional agricultural magazines. The findings indicated that the editors conceptualize risk in agriculture differently from how agricultural risks are reported in the mainstream media for the more general public; many emphasized the issues in terms of marketing or financial risk. Editors emphasized that they report on risk from an action angle, providing advice or information on how to mitigate the risk. The public’s perception of agriculture, advertisers, and personal topic preferences were cited as influencers of their risk coverage. When covering risk stories, agricultural publication editors prefer journalists who can write well and have an agricultural background or knowledge of the industry. Future research should be conducted to expand on the results from this exploratory study.
Keywords: agriculture; Gatekeepers; industry; financial risk; Publication; editors; decisions; Researcher